Electrical parameters and low-frequency noise of AlGaN/GaN high-electron mobility transistors with different channel orientation - de Andrade, Maria Glória Caño [UNESP] (2024)
The performance of AlGaN/GaN High-Electron Mobility Transistors (HEMTs) fabricated on 〈1 1 1〉 silicon substrates has been experimentally investigated, aiming to verify the effect of different channel orientations on the main electrical parameters, such as drain current (ID), threshold voltage, transconductance (gm), and Drain-Induced Barrier Lowering (DIBL). Moreover, the noise Power Spectral Density (PSD) with different channel orientations has also been characterized in linear operation. No noticeable differences on the electrical and noise PSD characteristics have been observed between the GaN channel orientations (0°, 90° and 45°).